The Influence of Self and Peer Assessment on Science Learning (Universitas Negeri Semarang, 2017)
Environmental conditions around the individual is very influential in this type of social learning patterns. The aims of this study were to identify the influence of self and peer assessment on science learning. This research used post test only control design. The result of the analysis of data Showed that; (1) 50% of the 30 students in the experimental class were able to do a self-assessment activities well; 56.67% of the 30 students in the experimental class were able to do peer assessment activities well; and 26.67% of the 30 students in the control class were able to do self-assessment activities well. (2) 100% of the 30 students in the experimental class were able to do a self-assessment of the science learning outcomes well; 93.3% of the 30 students in the experimental class were able to do peer assessment of the science learning outcomes well; and 73.3% of the 30 students in the control were able to obtain a good score of science learning outcomes according to the teacher assessment. The result results show that the application of self and peer assessment has an effect on students' learning activity and outcomes. The conclusion is that the application of self and peer assessment has an effect learning of science. It is necessary to exercise this assessment periodically during the learning activity. The research should combine students' assessment with that of reviews their teacher by 50% to obtain accurate learning outcomes.